2022
DOI: 10.1029/2021jd036095
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Impacts of Stratospheric QBO on the Global Circulation up to the Lower Thermosphere

Abstract: One of the important features of the middle atmosphere dynamics is the quasi-biennial oscillation (QBO) of zonal mean flows at stratospheric heights (e.g., Baldwin et al., 2001;Holton & Tan, 1980). This phenomenon is observed at equatorial latitudes: the direction of the zonal wind changes to the opposite with the period varying between 22 and 34 months. The highest zonal wind velocities are observed at altitudes of 20-30 km: about 20 m/s for westerlies and about 30 m/s for easterlies (Baldwin et al., 2001). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
(81 reference statements)
1
15
0
3
Order By: Relevance
“…The MUAM includes a parameterization of thermal and dynamical effects produced by mountain waves 32 and a spectrum of non-orographic gravity waves 33 . Numerous analyses have been carried out to validate MUAM, which have shown that it correctly reproduces the structure of the atmospheric circulation, PWs, and tides (e.g., 8,9,21,34,35 ), sudden stratospheric warmings 36 , as well as the resonance properties of the atmosphere (normal atmospheric modes) 20 .…”
Section: Methods and Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The MUAM includes a parameterization of thermal and dynamical effects produced by mountain waves 32 and a spectrum of non-orographic gravity waves 33 . Numerous analyses have been carried out to validate MUAM, which have shown that it correctly reproduces the structure of the atmospheric circulation, PWs, and tides (e.g., 8,9,21,34,35 ), sudden stratospheric warmings 36 , as well as the resonance properties of the atmosphere (normal atmospheric modes) 20 .…”
Section: Methods and Approachesmentioning
confidence: 99%
“…This variability in model simulations is interpreted as interannual 20,21 . Physical and hydrodynamic processes taken into account in the current version of the MUAM and the scheme of a numerical experiment are described in 8 .…”
Section: Methods and Approachesmentioning
confidence: 99%
“…Явление квазидвухлетнего колебания (КДК) экваториального зонального ветра является одной из важных особенностей динамики атмосферы [1]. Недавно на основе численного моделирования Коваль с соавторами [2] продемонстрировали, как изменения в структуре планетарных волн (ПВ) способствуют распространению эффектов КДК на полярные широты и в термосферу посредством модификаций потока Элиассена-Пальма (ЭП) и его дивергенции, и за счет образования вихревой меридиональной циркуляции.…”
unclassified
“…Для определения фаз КДК используется разложение наблюдаемых вариаций зонального потока на эмпирические ортогональные функции (ЭОФ). Такой подход позволяет учитывать вертикальную эволюцию фаз КДК и минимизировать неопределенности в определении фаз КДК [2]. Всего было определено 4 фазы КДК: восточная фаза (вКДК), переходная с восточной фазы на западную (взКДК), западная (зКДК) и переходная от западной к восточной фазе (звКДК).…”
unclassified
See 1 more Smart Citation